2005
DOI: 10.1021/ma0518611
|View full text |Cite
|
Sign up to set email alerts
|

Rational Control of Viscoelastic Properties in Multicomponent Associative Polymer Networks

Abstract: We report here the formation and dynamic mechanical properties of metallo-supramolecular networks formed by mixtures of bis-Pd(II) and Pt(II) cross-linkers with poly(4-vinylpyridine) in DMSO. Precise control over the dynamic mechanical properties of the bulk materials is achieved through the dissociation kinetics of the metal-ligand coordination bond responsible for cross-linking, the density of the cross-links, and the relative amounts of multiple cross-links. In networks formed from multiple types of cross-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
116
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(124 citation statements)
references
References 50 publications
7
116
0
Order By: Relevance
“…6, may be attributed to the multicomponent nature of the cross-linking in these systems, as both LMWH-LMWH and PF4 ZIP -LMWH interactions determine the rheological character of the gels. The resistance to flow in hydrogels is determined by the slower crosslinkers [66], and in SPR experiments. In SPR experiments, the LMWH-LMWH interactions are suggested to be much slower than PF4 ZIP -LMWH interactions (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…6, may be attributed to the multicomponent nature of the cross-linking in these systems, as both LMWH-LMWH and PF4 ZIP -LMWH interactions determine the rheological character of the gels. The resistance to flow in hydrogels is determined by the slower crosslinkers [66], and in SPR experiments. In SPR experiments, the LMWH-LMWH interactions are suggested to be much slower than PF4 ZIP -LMWH interactions (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…In an early series of papers, Stadler and Freitas 11,[22][23][24] studied the rheological behavior of polybutadienes lightly modified with double-hydrogen-bonding phenylurazole groups, finding that even with light substitution along the backbone the storage modulus plateau was broadened and shifted to lower frequencies (although the overall network properties were primarily dictated by the highly entangled polymer backbone and the crystallization of the phenyl urazole side chains). More recently, reversible networks based on metal-ligand coordination have been synthesized and the macroscopic material properties directly related to the coordination dynamics; [25][26][27][28] in this case it was found that formation of a strong network required not just a high association constant but also slow dynamics of the reversible bond. Additionally, supramolecular gels based on hydrogen bonding in ionic liquids have been demonstrated and their rheological properties related to the strength and number of hydrogen bonds as well as stoichiometry of donor and acceptor units.…”
Section: Introductionmentioning
confidence: 99%
“…Most experimental systems seem to be kinetically limited, and this is the case treated by almost all published analytic theories for reversibly associating networks, including transient network models [22,25]. Theories for kinetically limited AP networks [20,21,24,26,27] assume that the sticky bond lifetime τ sb is so long compared to all "polymeric" relaxation times that it controls all important time scales for network relaxation, and therefore that kinetics only affect key network relaxation times through their effect on τ sb (or, alternately, as suggested by recent experiments [50,51], the inverse dissociation rate constant k −1 b , defined below). We show that the validity of this assumpton is questionable, and that there is a wide parameter space, plausibly accessible in experiments, where it is invalid.…”
Section: Introductionmentioning
confidence: 99%